2015
DOI: 10.1021/acscatal.5b01479
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Aerobic Oxidation of Alcohols and Amines to Imines

Abstract: Imines as valuable intermediates are widely applied in pharmaceutical syntheses and organic transformation. However, the traditional imine synthesis involves unstable aldehydes, dehydrating agents and Lewis acid catalysts. The topic of review is focused on three new approaches, namely, the cross-coupling of alcohols with amines, the self-coupling of primarily amines, and the oxidative dehydrogenation of secondary amines, utilizing much more readily available starting materials and green oxidant (O 2 /air) to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
251
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(263 citation statements)
references
References 168 publications
2
251
0
1
Order By: Relevance
“…This can be attributed to two competing dehydrogenation and transamination pathways observed in the case of primary amine as substrates. Further investigation revealed that it is the nature of the catalytic species that plays a prominent role in altering the predicted selectivity in oxidative dehydrogenation (Scheme a) . However, this oxidative dehydrogenation method does not apply to tertiary amines.…”
Section: Nitriles and Iminesmentioning
confidence: 98%
See 1 more Smart Citation
“…This can be attributed to two competing dehydrogenation and transamination pathways observed in the case of primary amine as substrates. Further investigation revealed that it is the nature of the catalytic species that plays a prominent role in altering the predicted selectivity in oxidative dehydrogenation (Scheme a) . However, this oxidative dehydrogenation method does not apply to tertiary amines.…”
Section: Nitriles and Iminesmentioning
confidence: 98%
“…In parallel, Gao et al. reviewed aerobic oxidation of alcohols and amines to imines . This review, on the other hand, gives a comprehensive picture of ruthenium‐catalyzed aerobic oxidation of amines.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various heterogeneous catalytic procedures have been designed around the world due to the growing interest in renewable catalysis. In this regard, like various organic transformation reactions, the amine to imine formation reactions have gained much attention due to their vast industrial applications in preparing heterocyclic compounds, pharmaceuticals, biologically active materials, and fine chemicals . Conventionally, imines are produced from condensation reactions of amines and aldehydes in the presence of various dehydrating agents, bases, or Lewis acids .…”
Section: Aerobic Oxidative Coupling Of Amines To Synthesize Imines Inmentioning
confidence: 99%
“…The effects of reaction variables such as temperature, time, pressure and molar ratio of epoxide to catalyst on the catalytic performance were systematically investigated. These bifunctional catalysts were found to be highly stable to moisture and oxygen, resistant to impurities, and recyclable with only minor losses in catalytic activity …”
Section: Schiff Base Complexes As Catalystsmentioning
confidence: 99%